The origin of the relationship betweens science, technology and the State of Ecuador - Edwin Fernando Herrera García (Trilogía Ciencia Tecnología Sociedad, 2017)
this paper analyzes the first two attempts at the creation of science and technology policy in Ecuador from the role of various stakeholders: scientists, politicians, and industry. The institutionalization of this policy first emerged in 1973 as part of the “nationalist and revolutionary” military dictatorship of Rodriguez Lara, and as part of the proposed import substitution industrialization (ISI) in response to the oil boom. The second attempt took place during the return to democracy in 1979 and was based on the enactment of the Law on the National System of Science and Technology and on the creation of the Consejo Nacional de Ciencia y Tecnología. This paper discusses the narrative of the events rather than the cause. It examines social macro processes through the lens of various stakeholders (political and economic national conditions and international influences). Furthermore, the definition and implementation of policies is explained via political cultures; implicit and explicit scientific technology Policy; and technological scientific paradigms.